Shake table testing of a two-story CLT platform building - Furley, Jace, author; van de Lindt, John, advisor; Heyliger, Paul, committee member; Cutler, Harvey, committee member (Colorado State University. Libraries, 2018)
Cross Laminated Timber (CLT) is an engineered, prefabricated, wood product that is well established in the European construction market, and has seen increasing usage in North America. In the U.S., CLT's application has been mostly limited to low seismic regions due to its exclusion from current seismic design standards, requiring designers to apply alternative design methods, and ultimately undermining its economic competiveness in some cases. This thesis presents the method and results from a full-scale two-story CLT platform building test conducted at the NHERI@UCSD Shake Table in San Diego, California. The testing was divided into three phases, with each phase testing a different wall configuration. The first two phases investigated the effects of different CLT panel aspect ratios (height:width) on the performance and behavior of the structure, with aspect ratios of 3.5:1 and 2.1:1 being tested respectively. The third phase used the same 3.5:1 aspect ratio CLT panels as the first phase, but introduced transverse walls to document the behavior of a more realistic building system. The Equivalent Lateral Force (ELF) procedure was used in the design of the stacked CLT shear walls, with the assumption that shear was resisted entirely by generic angle brackets, and the overturning moment was resisted by tie-down rods on either end of each shear wall. The structure was subjected to several different intensities of the 1989 Loma Prieta ground motion record, with the largest motion having a return period of approximately 2500 years. Life-safety is the primary objective of current seismic design in the U.S., and all three phases of testing showed no risk of collapse. The test results provided information on the dynamic behavior of platform style CLT construction with stacked shear walls.
Keywords: seismic force resisting system; cross laminated timber; shake table